Artefacts that travel: the changing contexts and meanings of archaeological objects collected by Edward J. Dunn - Parsons, I. (Southern African Humanities, 2013)
This paper considers archaeological artefacts collected by the geologist, E.J. Dunn, during the 1870s in the Griquatown area of the present-day Northern Cape Province, South Africa, and housed in the Pitt Rivers Museum, Oxford, since 1936. Analysis of these artefacts is constrained by uncertainty regarding their provenance and association. The focus here is therefore on the biography of a small number of lithic objects within the collection to consider how their uses and meaning have changed as the objects moved from one physical context to another. The recognition that some of Dunn’s Griquatown lithics may well belong to the Mossel Bay and/or Fauresmith archaeological industries of South Africa, and are unlikely to have been manufactured by the San as he thought, is one noteworthy outcome of their closer consideration.